2009
DOI: 10.1007/s10549-009-0663-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular predictors of efficacy of adjuvant weekly paclitaxel in early breast cancer

Abstract: Both subtype classifications yielded prognostic and predictive information. HR +/HER2- patients (and Luminal A patients) had a significantly better outcome than the other subgroups of patients. The superiority of FEC-P over FEC was clearly more marked in HR-/HER2- patients (TN patients), particularly in the subset with basal phenotype (TN and either EGFR+ or cytokeratins 5/6+). The Luminal A subtype also achieved a significant benefit with FEC-P. The molecular-defined subgroup of TN was clearly predictive of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 24 publications
2
56
0
Order By: Relevance
“…No DFS advantage was seen in the luminal A population [22]. Similarly, the GEICAM 9906 trial comparing FEC to FEC followed by weekly paclitaxel, found that the paclitaxel benefit was mainly concentrated in the triple negative/basal-like patient population [65]. However, all these studies have the disadvantage of having compared multi-drug regimens and, as such, attributing benefit to any of drug individually becomes very difficult.…”
Section: Discussionmentioning
confidence: 99%
“…No DFS advantage was seen in the luminal A population [22]. Similarly, the GEICAM 9906 trial comparing FEC to FEC followed by weekly paclitaxel, found that the paclitaxel benefit was mainly concentrated in the triple negative/basal-like patient population [65]. However, all these studies have the disadvantage of having compared multi-drug regimens and, as such, attributing benefit to any of drug individually becomes very difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no standard chemotherapy regimen that specifically applies to women with triple-negative breast cancers, anthracycline and taxane-based chemotherapy remains the most commonly used regimen, especially since taxanes have significant activity in the treatment of triple-negative breast cancers [9][10][11]. As an example, in the GEICAM 9906 trial of 5-fluorouracil, epirubicin, and cyclophosphamide (FEC) versus FEC followed by paclitaxel, the addition of paclitaxel was associated with a significant improvement in disease-free survival at seven years (74 versus 56 percent, respectively) [11]. Our patients were treated by 3 cycles FEC followed by 3 cycles of decetaxel.…”
Section: Discussionmentioning
confidence: 99%
“…21 Efficacy of paclitaxel specifically for TNBC (compared with non-TNBC) has been observed in subtype analyses within clinical trials. 24,25 However, these associations between TNBC and taxanes have not been consistent; a meta-analysis has shown benefit for taxane in the adjuvant setting independent of ER status. 26 Ixabepilone is an epothilone B analogue that stabilizes microtubules and has activity in patients with TNBC as a monotherapy.…”
Section: Microtubule-targeting Agentsmentioning
confidence: 99%